Jacob have I loved - Paterson, Katherine (New York : HarperTrophy, 1990)
Feeling deprived all her life of schooling, friends, mother, and even her name by her twin sister, Louise finally begins to find her identity.
Newbery Medal/Honor.
Wilson's Junior High School.
Wilson's Senior High School.
Book Links (A.L.A.), September 2005.
Booklist, January 2007.
Christian Library, June 2006.
Keywords: Individuality -- Fiction; Sisters -- Fiction; Twins -- Fiction; Individuality -- Fiction; Sisters -- Fiction; Twins -- Fiction; Chesapeake Bay Region (Md. and Va.) -- Fiction; Chesapeake Bay Region (Md. and Va.) -- Fiction